A Common man's guide to the Common Market : the European Community - Arbuthnott, Hugh.; Edwards, Geoffrey; Federal Trust for Education and Research (London : Macmillan for the Federal Trust, 1979)
The aim of the book is to examine the primary objective of the European Community and the mechanisms and policies which have been adopted to achieve these objectives
Includes bibliographies and index.
osc 14/11/2018
Loans
Keywords: International Trade; International economic relaions